2012
DOI: 10.1161/strokeaha.111.626200
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Arterial Wall Characteristics Are Associated With Incident Ischemic Stroke But Not Coronary Heart Disease in the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background and Purpose Ultrasound measurements of arterial stiffness are associated with atherosclerosis risk factors, but limited data exist on their association with incident cardiovascular events. We evaluated the association of carotid ultrasound derived arterial stiffness measures with incident coronary heart disease (CHD) and ischemic stroke in the ARIC study. Methods Carotid arterial strain (CAS) and compliance (AC), distensibility (AD) and stiffness indices (SI), pressure-strain (Ep) and Young’s elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 35 publications
(38 reference statements)
3
91
0
Order By: Relevance
“…Also, the age-sex interaction in DC means that older women have stiffer arteries than older men. To give a sense of the magnitude of the differences, we use the unadjusted hazard ratios for stroke associated with lower distensibility reported by Yang et al 7 : because of differences in DC, women who are 10 years older would have a 30.4% higher hazard of stroke than their younger counterparts, whereas men with the same age difference would have a 25.6% higher hazard of stroke. In addition, the afterload on the heart of older women is likely to be greater than that among older men.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the age-sex interaction in DC means that older women have stiffer arteries than older men. To give a sense of the magnitude of the differences, we use the unadjusted hazard ratios for stroke associated with lower distensibility reported by Yang et al 7 : because of differences in DC, women who are 10 years older would have a 30.4% higher hazard of stroke than their younger counterparts, whereas men with the same age difference would have a 25.6% higher hazard of stroke. In addition, the afterload on the heart of older women is likely to be greater than that among older men.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are known to have a number of immunomodulatory effects which may affect arterial stiffness [11][12][13][14] and plaque stability 15,16) . Ultrasound-based techniques have been used for non-invasive assessment of the distensibility of arteries, such as the carotid artery, which is fairly superficial in its location 17) . Despite being a quicker and rela-…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound--based carotid stiffness measurements are valuable because they make it possible to determine arterial stiffness in the vessel with the most relevance to particular cerebrovascular outcomes. It was recently shown that local carotid stiffness had independent predictive value for incident stroke, but not for coronary heart disease [25]. In the present study, carotid arterial stiffness was assessed in patients with concentric hypertrophy -the pattern associated with a higher prevalence of carotid atherosclerosis and cerebrovascular events.…”
Section: Arterial Stiffness and LV Concentric Geometrymentioning
confidence: 82%